Xerothermic and anthropophytic species populations in the grassland communities of “Skarpy Ślesińskie” Nature Reserve and its surroundings - Ratyńska, Halina; Waldon, Barbara; Boratyński, Adam (Biodiversity: Research and Conservation, 2006)
Nature Reserve “Skarpy Ślesińskie” and adjacent areas are the most important refuge of the thermophilous flora on the boundary of the Wielkopolska and Pomerania regions. The flora and vegetation of xerothermic grasslands, meadows and pastures and groves among them were investigated in that region. The field data were collected on the south-facing slopes of the Noteć river valley between Trzeciewnica and Ślesin. Arabis hirsuta, Aster amellus, Astragalus cicer, Medicago minima, Seseli libanotis, S. annuum and Trifolium rubens reported in the previous floras of the region have not been confirmed in the field. Asperula tinctoria, Gentiana cruciata, Vicia tenuifolia and Viscaria vulgaris were found for the first time. Grassland communities included the greatest number of the alien species (43). It can be explained by the relatively low plant coverage, the neighbourhood of the field and a small distance to the railway.